The place and purpose of mathematics within post-16 vocational pathways - Dalby, Daine (2014)
Recent policy changes continue to raise the profile of mathematics in post-16 education but the integration of this seemingly academic subject within the context of vocational education remains challenging. In this paper evidence from a multi-method study of vocational students in Further Education will be used to examine the impact of both isolated and integrated practices regarding the provision of a functional mathematics curriculum. Historically the relationship between mathematics and vocational education has been uneasy. Successive curricula have favoured either an embedded approach, which prioritises vocational relevance, or a view which has focussed on the acquisition of a common core of basic mathematical processes. This research shows the positive impact on students when a curriculum which emphasised the usefulness of mathematics for life and work was used in conjunction with internal policies that promoted an integrated, rather than an isolated, organisational approach. Mathematics that students perceived as relevant to their current values and vocational destinations led to more positive attitudes and greater engagement. Comparisons of case studies of student groups in three large Further Education colleges will be used to show how functional mathematics was positioned with respect to different vocational programmes and how opportunities for vocational relevance were maximised in some departments. Many of these students had low levels of attainment and enthusiasm for mathematics but grasping the purpose of mathematics and the place it may have in their future lives were key factors that contributed to significant change.